Peran Teknologi dalam Pembelajaran Pendidikan Agama Hindu - Ida Ayu Gde Wulandari; I Made Putra Aryana; I Gede Eka Surya Kanta (Jurnal Pendidikan Agama, 2022)
The development of technology is an essential phenomenon that has a significant impact on all dimensions of life. Technological developments are multi-interpretative. In a certain perspective, technology has been considered capable of giving meaning and benefits to human life. Seeing from the perspective and interpretation as well as the correlation of technology with human existence and its relationship with the objectives of the UU Sisdiknas No. 20 Tahun 2003, the positive impacts generated by technology are very numerous and important. When connected to the era of technology 4.0 and towards the era of society 5.0, there is a need for technological literacy so that can be useful among educators and students. The method in this paper is literature study. Literature studies are related to theoretical studies and other references related to values, culture, and norms that develop in the social situation. Learning technology was originally seen as equipment technology, which is related to the use of equipment, media and means to achieve educational goals. Learning technology is a combination of three streams of mutual interest, namely media in education, psychology of learning and systems approach in education. the role of technology in learning Hindu religious education can support learning outcomes. This is influenced by the method and selection of media that support the learning process. With various characteristics of children, the selection of media that is considered interesting and makes it easier for students to accept the lessons delivered, the teacher will be helped by the existence of this technology.